An Mise-en-Scène analysis on Confined Space Movies: Locke and Buried - Sivaji, Drishya; George, Amith; T, Varun Prabha; T, Varun Prabha (International Journal of Psychosocial Rehabilitation, 2020)
Cinema is an art a visual art form that allows the filmmakers to tell a story using various multimedia, allows a writer and a director, with help from other perspective. Researches show that cinema is a pretty young art form, created around the 19th Century. Mise-en-scene is the mix of arts that this paper just mentioned. With a literal meaning of “placing on stage”, mise-en-scene elements are crucial for any cinema or moving picture (movie) that is getting produced. These elements include all that is needed in a cinema in front ofa camera that films it (Moura, G. (2010, August 15). Gabe Moura. Retrieved fromhttp://www.elementsofcinema.com/cinema/definition-and-brief-history/). Claustrophobic movies are fascinating because they pose challenges regarding the appropriate use of Mise-en-Scene elements. These movies are usually narrated through the process of captivity narration. Thus, a writer and movie director can grab the attention of audiences. For instance, buried (2010), a movie we are reviewing, employs a captivity narration through the main and only on-screen character’s ordeals. However, Locke (2013), needs a different type of narration based on its script and its nature. The paper will be attempting to analyze mise-en-scene elements of the movies Buried (2010) and Locke (2013) as they are two different types of claustrophobic movies.Keywords--,  , , , , , ,